Reading (about) The Polish People’s Republic: Justyna Tuszyńska and Dariusz Brzostek converse with Ryszard Ćwirlej - Ćwirlej, Ryszard; Brzostek, Dariusz; Tuszyńska, Justyna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Ryszard Ćwirlej: sociologist, journalist, and writer; former Polish Television reporter and editor-in-chief of the newscast Telekurier. A lecturer at the Faculty of Political Science and Journalism, Adam Mickiewicz University in Poznań. An author of numerous detective novels and an inventor of Polish “neo-militia literature”, a literary genre depicting the everyday life of the militiamen in the PRL (The Polish People’s Republic).